Diabetes mellitus como causa de amputação não traumática no Hospital de Clínicas da Universidade Federal de Uberlândia - Almeida, Ana Elizabeth Cunha Guimarães de (2008)
Diabetes mellitus is considered a major public health issue, since it is highly prevalent and its incidence has been progressively increasing the last years. The chronic complications of the diabetes are important cause of mortality and morbidity, complications that may include the amputation of the lower limbs. The current study has as an objective to verify the diabetes mellitus as a cause of non-traumatic amputation of the lower limbs, observing if the triggering factor of these amputations could be avoided, besides identifying the risk factors, observing the participation in diabetes education groups and compare the results with early research performed in the same institution. The 124 patients who had their lower limbs amputated by non-traumatic causes in the Hospital de Clínicas da Universidade Federal de Uberlândia were interviewed, prospectively, over 1 year. Of those patients, 53% were diabetic. The avarage sex and age didn t show difference between diabetic and nondiabetic (p=0.122 and p=0.604). In diabetic patients, 72.7% of the amputations were triggered by avoidable causes, there was a predominance of minor amputation (73.1%), most of the patients were type 2 diabetics (86.4%), with more than 10 years of diabetes diagnosis (59.1%) and were insulin-treated (60.6%) and most of them had never attended to an educational group for diabetes (57.6%), although 69.7% related having previously been given orientations on self-care of the feet. More than 80% of the diabetic were dosing capillary glycemia in health institutions and more than half were doing the exam monthly or even more sporadically .Obesity and overweight (p=0.001) were significantly more frequent on the diabetic rather than the non-diabetic patients. The diabetic also had the urea and creatinine levels higher than the non-diabetic patients. The majority of the amputated patients, despite of knowing it s importance and benefits, did not have physical activities as their habit. In nondiabetic patients, prevailed major amputation (58.2%) and there was higher association with smoking (p<0.001). The amputations etiology were predominantly mixed (infectious and ischemic). Diabetes mellitus is the main cause of non-traumatic amputation in our region, and most of the factors that trigger these amputations were of preventable causes.